Hospital Pharmacists and Antimicrobial Stewardship: A Qualitative Analysis - Lok Hang Wong; Evonne Tay; Shi Thong Heng; Huiling Guo; Andrea Lay Hoon Kwa; Tat Ming Ng; Shimin Jasmine Chung; Jyoti Somani; David Chien Boon Lye; Angela Chow (MDPI AG, 2021)
Antimicrobial stewardship programmes (ASPs) in hospitals are predominantly led by specific ASP physicians and pharmacists. Limited studies have been conducted to appreciate non-ASP-trained hospital pharmacists' perspectives on their roles in antimicrobial stewardship. Focus group discussions (FGDs) were conducted with 74 pharmacists, purposively sampled from the 3 largest acute-care public hospitals in Singapore, to explore facilitators and barriers faced by them in antimicrobial stewardship. Applied thematic analysis was conducted and codes were categorised using the social-ecological model (SEM). At the intrapersonal level, pharmacists identified themselves as reviewers for drug safety before dispensing, confining to a restricted advisory role due to lack of clinical knowledge, experience, and empowerment to contribute actively to physicians' prescribing decisions. At the interpersonal level, pharmacists expressed difficulties conveying their opinions and recommendations on antibiotic therapy to physicians despite frequent communications, but they assumed critical roles as educators for patients and their caregivers on proper antibiotic use. At the organisational level, in-house antibiotic guidelines supported pharmacists' antibiotic interventions and recommendations. At the community level, pharmacists were motivated to improve low public awareness and knowledge on antibiotic use and antimicrobial resistance. These findings provide important insights into the gaps to be addressed in order to harness the untapped potential of hospital pharmacists and fully engage them in antimicrobial stewardship.